Characterization Of Two Polyhydroxyalkanoate Synthase Genes (Phac) Of Cupriavidus Malaysiensis Usmaa1020t Isolated From Kulim Lake, Kedah, Malaysia - Shafie, Nur Asilla Hani (2021)
Cupriavidus malaysiensis strains USMAA1020T, USMAA2-4 and USMAHM13 were isolated from various natural environments of Peninsular Malaysia. USMAA1020T was isolated from sludge in Kulim Lake, Kedah. Meanwhile, USMAA2-4 was isolated from soil of Sungai Pinang, Penang whereas USMAHM13 was isolated from sludge of a paddy field in Sg. Manik, Perak. The 16S rRNA gene sequence similarity between USMAA1020T, USMAA2-4, and USMAHM13 was 99%. In phylogenetic analysis, these strains formed a cluster in phylogenetic tree constructed when using both maximum-likelihood and neighbour joining method. Till date, there were many reported Cupriavidus strains which have been characterized and identified but only limited information available on the whole genome sequence of Cupriavidus strains especially strains that contain two functional polyhydroxyalkanoate synthase genes (phaC). In this study, we analyzed the whole genome sequence of these strains which are closely related to each other regardless the differences of isolating environments. The whole genome sequences were done using the PacBio RS II platform. The genomes sequenced (7.82 to 8.70 Mb) were comparatively larger than the type strain Cupriavidus necator H16T (7.42 Mb). Two polyhydroxyalkanoates synthase genes (phaC) were found in the annotated genomes of all the three strains.